PENGEMBANGAN BAHAN AJAR KONTEN UNTUK MENINGKATKAN HASIL BELAJAR PEMBELAJARAN BERDIFERENSIASI PADA PELAJARAN INFORMATIKA KELAS XI SMA - Ratnaduhita, Nadiah Alma; Prasetya, Didik Dwi; Setiawan, Ahmad Yusuf; Wardani, Adi Wahyu; Ridlo, Muhammad Zidni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In order to enhance student learning outcomes and provide a more stimulating and productive learning environment, this study intends to create content-differentiated teaching materials based on the ADDIE instructional design approach. According to preliminary observations, the material's vocally presented and text-heavy structure made it difficult for students to understand and often caused disengagement. The researcher created animated videos and a flipbook as additional learning resources to solve this problem. The created materials' high to exceptional quality was validated by media and subject-matter experts. All participants in the implementation phase, which was conducted with 36 students in Class XI-6, successfully attained learning mastery. Formative assessments, which included a pre-test given via Quizizz, worksheets (LKPD), and a post-test, showed a significant increase in student performance. In summary, the content-differentiated teaching resources were found to be legitimate and successful in raising student performance and encouraging a more engaging and joyful learning environment.